Lessons from the health policies for children during the pandemic in Japan - Naohisa Shobako (Frontiers Media S.A., 2022)
It is everyone's desire to seek the sound growth of children through food education and there is a critical need for fostering an environment for this purpose. Health policies are important for this support. To the present, the Japanese society has been greatly disrupted by COVID-19 pandemic. "Stay at home", "mokusyoku (silent eating)", and mask wearing were encouraged in nationwide campaigns as public health measures to combat COVID-19. There are some papers reporting negative effects of "stay at home" and lockdowns such as weight gain, decrease in physical activities and change in eating habits. In Japan, while benefits and advantages of food education during mealtime were previously well studied, the "mokusyoku" rule may directly run counter to this food education. Moreover, there are several reports showing that nutrients might contribute to prevention of infectious diseases. Japanese children were also encouraged to wear masks all day long. The results of the clinical research, especially randomized control trials, show limited protective effect of masks. On the other hand, negative outcomes of the masks were reported in various scenes. This review focuses on these topics and arousing reconsideration for a better environment for children.